Role of IL-25 on Eosinophils in the Initiation of Th2 Responses in Allergic Asthma - Peng, Bo; Sun, Lin; Zhang, Meng; Yan, Huacheng; Shi, Guochao; Xia, Zhenwei; Dai, Ranran; Tang, Wei (Frontiers in Immunology, 2022)
Background: Eosinophils act as a secondary antigen-presenting cell (APC) to stimulate Th cell responses against antigens. IL-25 plays an important role on eosinophil activation in allergic asthma. The role of IL-25 on the classic APC functions of dendritic cells has been elucidated. However, whether IL-25 facilitates eosinophils for antigen presentation is unknown. Objective: To elucidate the role of IL-25 on eosinophils antigen presenting function during allergic asthma and its related mechanism. Methods: Eosinophils from allergic asthma subjects were cultured with IL-25 and HDM to identify the co-stimulator molecules expression. Co-cultures of patient eosinophils and autologous naïve CD4+ T cells in the same culture system were to explore whether eosinophils had the capacity to promote Th cell differentiation in response to IL-25 engagement. In asthma mouse model, IL-25-/- mice were exposed to HDM to investigate the effect of IL-25 on eosinophils during sensitization phase. The impact of IL-25 on the capacity for eosinophil taking up antigens was evaluated. Mouse bone marrow derived eosinophils (BmEOS) were co-cultured with naïve CD4+T cells sorted from spleens under HDM and IL-25 stimulation to identify T cell differentiation. Results: IL-25 upregulated HLA-DR, PD-L1 and OX-40L expression on eosinophils from allergic asthma patients. IL-25 and HDM co-sensitized eosinophils promoted Th2 differentiation. In mouse model, IL-25-/- mice experienced restrained allergic pulmonary inflammation and reduced eosinophils recruitment and antigen uptake capacity during early sensitization phase. In vitro, IL-25 promoted antigen uptake by eosinophils. In BmEOS and naïve CD4+T cells co-culture, IL-25 accreted the proportion of CD4+Th2 cells, which was absent in CD4+T cells culture alone. Conclusion: Our data identify a novel role of IL-25 in enhancing eosinophils antigen uptake and co-stimulator molecules expression to induce Th2 priming in the context of allergic inflammation.